2021
DOI: 10.21203/rs.3.rs-113216/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Material diets for Climate-Neutral Buildings

Abstract: The climate crisis is urging us to act fast. Buildings are a key leverage point to reduce greenhouse gas (GHG) emissions, but the embodied emissions related with their construction remain often the hidden challenge of any ambitious policy. Since a complete material substitution is not possible, we explore in this paper a material greenhouse gas (GHG) compensation where fast growing bio-based insulation materials are used to compensate building elements which necessarily release GHG. Different material diets as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…W ąs et al (2021) [11] , analyzed the impact of greenhouse gas emission reductions in farm sector in Poland; Becker et al (2020) [16] showed benefits of reducing emissions in the French spirits sector; and the research of Scuderi et al (2021) [17] concentrated on carbon footprint in conventional, organic, and zero-residue potato cultivation in Sicily. The research of Franzoi et al (2021) [18] and Carcassi et al (2021) [19] concerns neutrality in construction. Zachariadis et al (2021) presented energy efficiency measures and approached how to assess and prioritize the most energy-efficient projects in the building sector [20].…”
mentioning
confidence: 99%
“…W ąs et al (2021) [11] , analyzed the impact of greenhouse gas emission reductions in farm sector in Poland; Becker et al (2020) [16] showed benefits of reducing emissions in the French spirits sector; and the research of Scuderi et al (2021) [17] concentrated on carbon footprint in conventional, organic, and zero-residue potato cultivation in Sicily. The research of Franzoi et al (2021) [18] and Carcassi et al (2021) [19] concerns neutrality in construction. Zachariadis et al (2021) presented energy efficiency measures and approached how to assess and prioritize the most energy-efficient projects in the building sector [20].…”
mentioning
confidence: 99%